Semi-transparent thin film solar cells by a solution process - Chu, Van Ben; Park, Se Jin; Park, Gi Soon; Jeon, Hyo Sang; Hwang, Yun Jeong; Min, Byoung Koun (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2016)
Easily processed, low cost, and highly efficient solar cells are desirable for photovoltaic conversion of solar energy to electricity. We present the fabrication of precursor solution processed CuInGaS2 (CIGS) thin film solar cells on transparent indium tin oxide (ITO) substrates. The CIGS absorber film was prepared by a spin-coating method, followed by two successive heat treatment processes. The first annealing process was on a hot plate at 300 A degrees C for 30 min in air to remove carbon impurities in the film; this was followed by a sulfurization process at 500 A degrees C in an H2S(1%)/Ar environment to form a polycrystalline CIGS film. The absorber film with an optical band-gap of 1.52 eV and a thickness of about 1.1 A mu m was successfully synthesized. Because of the usage of a transparent glass substrate, a bifacial CIGS thin film device could be achieved; its power conversion efficiency was measured to be 6.64% and 0.96% for front and rear illumination, respectively, under standard irradiation conditions.